Influence of Bi2O3/WO3 substitution on the optical, mechanical, chemical durability and gamma ray shielding properties of lithium-borate glasses. Issue 4 (15th February 2021) - Stalin, Salavadi; Gaikwad, D.K.; Al-Buriahi, M.S.; Srinivasu, Ch; Ahmed, Shaik Amer; Tekin, H.O.; Rahman, Syed
Abstract: Six different lithium bismuth boro-tungstate glasses with chemical composition 20Li2 O-(20-x)Bi2 O3 -xWO3 -60B2 O3 (x = 0, 1, 2, 3, 4 and 5 mol%) were produced by the quenching method. Then, the glasses were investigated by means of their optical, mechanical, chemical durability and gamma ray shielding properties. Measured values of density and ultrasonic velocities were used to determine the elastic properties of the glasses. The optical band gap determined using the absorbance spectrum fitting (ASF) model was found to decrease under Bi2 O3 /WO3 substitution. The presence of BO3, BO4, BiO6, and WO4 structural groups in the glasses was confirmed by Fourier transform infrared spectroscopy (FTIR). The dissolution rate in the glass 20Li2 O–15Bi2 O3 –5WO3 –60B2 O3 (LBWB5) was found to be 10 times lower than 20Li2 O-20Bi2 O3 – 60B2 O3 . Mass attenuation coefficients (MAC) values of the produced glasses were determined using the MCNPX Monte Carlo code and Phy-X/PSD program. The photon attenuation parameters such as half value layer (HVL), mean free path (MFP), effective atomic number (Zeff ), exposure buildup factor (EBF) and energy absorption buildup factor (EABF) were also studied. The obtained results showed that Bi2 O3 /WO3 substitution has a direct impact on the photon attenuation abilities of produced glasses. More specifically, HVL values increased from 0.252 × 10 −2  cm for LBWB0 glass to 0.275 × 10 −2  cm for LBWB5 glass. However, different trends were observed for the photon buildup factors for the produced glasses. It can be concluded that the produced glasses have promising structural, optical, and photon attenuation properties to be used for gamma shielding applications.